Determination of the conformation of the key intermediate in an enantioselective palladium-catalyzed allylic substitution from residual dipolar couplings - Böttcher, Benjamin; Schmidts, Volker; Raskatov, Jevgenij; Thiele, Christina M. (Angewandte Chemie. International edition, 2010)
Hide and seek! The reactive intermediate in the title reaction has eluded conventional structure determination for years. With the help of residual dipolar couplings the conformation in solution could be determined (see picture). The sensitive intermediate was aligned in a liquid-crystalline phase containing poly(γ-benzyl-L-glutamate), and the orientation of the ligands was determined through local order tensors.